Biomimetic Silk Fibroin Hydrogels Strengthened by Silica Nanoparticles Distributed Nanofibers Facilitate Bone Repair. Issue 9 (10th March 2021) - Cheng, Yuet; Cheng, Gu; Xie, Congyong; Yin, Chengcheng; Dong, Xiangyang; Li, Zhi; Zhou, Xue; Wang, Qun; Deng, Hongbing; Li, Zubing
Abstract: Various materials are utilized as artificial substitutes for bone repair. In this study, a silk fibroin (SF) hydrogel reinforced by short silica nanoparticles (SiNPs)‐distributed‐silk fibroin nanofibers (SiNPs@NFs), which exhibits a superior osteoinductive property, is fabricated for treating bone defects. SF acts as the base part of the composite scaffold to mimic the extracellular matrix (ECM), which is the organic component of a native bone. The distribution of SiNPs clusters within the composite hydrogel partially mimics the distribution of mineral crystals within the ECM. Incorporation of SiNPs@NFs enhances the mechanical properties of the composite hydrogel. In addition, the composite hydrogel provides a biocompatible microenvironment for cell adhesion, proliferation, and osteogenic differentiation in vitro. In vivo studies confirm that the successful repair is achieved with the formation of a large amount of new bone in the large‐sized cranial defects that are treated with the composite hydrogel. In conclusion, the SiNPs@NFs‐reinforced‐hydrogel fabricated in this study has the potential for use in bone tissue engineering. Abstract : Incorporation of short silica nanoparticles (SiNPs)‐distributed‐silk fibroin nanofibers (SiNP@NFs) to the SF hydrogel crosslinked by horseradish peroxidase (HRP)/ hydrogen peroxide (H2 O2 )improves the mechanical properties and osteoinductive ability of the composite hydrogel. The composite hydrogel facilitates osteogenic differentiation of preosteoblasts and enhances new bone formation in the large‐sized cranial defects. Therefore, the SiNP@NFs‐reinforced‐hydrogel fabricated in this study has potential for application in bone tissue engineering.